Analysis of The Effect of Electronic-Based Payment Systems and Economic Growth in Indonesia - Mashabi, M; Wasiaturrahma, Wasiaturrahma (Jurnal Ilmu Ekonomi Terapan, 2021)
This research aims to analyze the effect of electronic payment systems based on credit cards, debit cards, and electronic money, as well as macroeconomic variables namely the money supply (M1), price level, and velocity of money towards real gross domestic product as a proxy for economic growth. The estimation carried out in this journal uses the Vector Error Correction Model (VECM) with period time series data of 2010:1-2018:12. The results of the journal show that doing debit card and electronic money-based transactions has a significant positive effect on economic growth in Indonesia in the long run. Keywords : Electronic payment systems, electronic money, credit cards, debit cards, economic growth, Vector Error Correction Model (VECM)  JEL : O470 C320